2015
DOI: 10.1002/jhm.2342
|View full text |Cite
|
Sign up to set email alerts
|

Insights into inpatients with poor vision: A high value proposition

Abstract: Background Vision impairment is an under-recognized risk factor for adverse events among hospitalized patients, yet vision is neither routinely tested nor documented for inpatients. Low-cost ($8 and up) non-prescription ‘readers’ may be a simple, high-value intervention to improve inpatients’ vision. We aimed to study initial feasibility and efficacy of screening and correcting inpatients’ vision. Methods From June 2012 through January 2014 we began testing whether participants’ vision corrected with non-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…Providing access to corrective lenses for patients with insufficient vision in the hospital setting is not infeasible. For instance, in our work, among the patients not wearing corrective lenses, we have shown that low-cost “readers” lenses correct the vision for the majority of patients with poor vision, including patients 65 years and older (Press et al, 2015). Despite the growing recognition of poor vision among inpatients, it is still unknown whether poor vision among hospitalized older patients is associated with worse outcomes after hospitalization.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Providing access to corrective lenses for patients with insufficient vision in the hospital setting is not infeasible. For instance, in our work, among the patients not wearing corrective lenses, we have shown that low-cost “readers” lenses correct the vision for the majority of patients with poor vision, including patients 65 years and older (Press et al, 2015). Despite the growing recognition of poor vision among inpatients, it is still unknown whether poor vision among hospitalized older patients is associated with worse outcomes after hospitalization.…”
Section: Introductionmentioning
confidence: 68%
“…For instance, low HL may lead to decreased awareness of, and/or access to, vision care to improve vision level; vision screening may aid in overcoming HL barriers and improve awareness of and access to vision care post-hospital discharge. In addition, correcting vision may contribute to improved self-efficacy that could lead to improved HL; given that a significant percentage of hospitalized patients with insufficient vision can have their vision corrected by cost-effective interventions such as “readers” lenses, this is a promising finding (Press et al, 2015). Future work could explore the extent to which vision and low health literacy interact.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 This is salient, because both the health literacy assessment and the cognitive battery require participants to be able to see text. In prior research, we documented that patients 65 years and older have a dual risk for poor health literacy and poor vision when compared to their younger counterparts.…”
Section: T O the Editorsmentioning
confidence: 99%
“…2 Further, at our institution, we have found that nearly half of hospitalized participants 65 years and older have poor vision (compared to about one-quarter among participants under 65). 3,4 This is salient, because both the health literacy assessment and the cognitive battery require participants to be able to see text. In prior research, we documented that patients 65 years and older have a dual risk for poor health literacy and poor vision when compared to their younger counterparts.…”
Section: T O the Editorsmentioning
confidence: 99%
“…The ideal screening tool, therefore, should be brief, simple to score, and have easily reportable results that can be incorporated into the electronic health record (EHR). Further, since adequate vision and literacy are known barriers to administering screening tools to hospitalized patients, an ideal HL screening tool would be verbally administered to avoid problems with seeing or processing written materials (Press et al, 2015; Press, Shapiro, Mayo, Meltzer, & Arora, 2013). Another barrier to wide-spread screening has been identifying an effective screening tool.…”
Section: Introductionmentioning
confidence: 99%